ANALISIS PROMOSI TERHADAP DANA PIHAK KETIGA DI PERBANKAN SYARIAH - Tria Yolanda (Tamwil, 2020)
The purpose of this research is to describe the promotion analysis of third party funds in syriah banking. The type of research used is literature review. which contains theoretical theories that are relevant to research problems. The results of this study can be concluded that in increasing third party funds through promotion can be done: Advertising, Sales Promotion, Personal Selling, Public Relations (Public Relations) , Direct Marketing (Direct Marketing)